2011
DOI: 10.1177/1557988310389165
|View full text |Cite
|
Sign up to set email alerts
|

Correlations With Satisfaction Measures in Men Treated With Phosphodiesterase Inhibitors for Erectile Dysfunction

Abstract: This literature review examined the relationship of erectile function to patient satisfaction. Published correlation coefficients ( r values) were sought between patient-reported outcomes (PROs; i.e., instruments/questionnaires) assessing erection or erectile function and PROs assessing individual sexual satisfaction, satisfaction in the context of the couple or relationship, or satisfaction with erection. The U.S. National Library of Medicine’s PubMed database was searched for English-language, randomized, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…Increased erection hardness could be the main parameter, leading to improved confidence . All results obtained at the end of the survey showed that increased erection hardness was correlated to significant improvement in self‐esteem, sexual and overall relationship, and overall satisfaction of the patient, in agreement with results of previous clinical trials .…”
Section: Discussionsupporting
confidence: 87%
“…Increased erection hardness could be the main parameter, leading to improved confidence . All results obtained at the end of the survey showed that increased erection hardness was correlated to significant improvement in self‐esteem, sexual and overall relationship, and overall satisfaction of the patient, in agreement with results of previous clinical trials .…”
Section: Discussionsupporting
confidence: 87%
“…According to Potts (2000, p.90), “the absence of—or difficulty in ‘achieving’ and ‘maintaining’— a robust ‘hard on’ in appropriate circumstances presents as a disastrous affliction in the male—an abnormality, a failure to stand up and be counted as a ‘real’ man.” In this context, many men experiencing erectile dysfunction (ED) never seek treatment for their condition, and those men who do often wait until their symptoms become too severe to ignore (Burns & Mahalik, 2007; Sand et al, 2008e). When men are willing to seek help, they are sufficiently motivated by their distress to entertain a wide range of potential treatments, including changes in diet and exercise, smoking cessation, cutting alcohol and drug use, periodontal treatment, herbs (e.g., red ginseng), acupuncture, natural hormones (e.g., DHEA) and amino acids (e.g., L-arginine), psychological counseling, prescription medications (e.g., Viagra), urethral suppositories, topical creams, testosterone replacement therapy, vacuum pumps, penile injection therapy, external penile prostheses, penile implants, vascular reconstructive surgery, stem cell therapy, platelet-rich plasma therapy, penile shockwave therapy, and penile transplants (Brubaker & Johnson, 2008; Burnett et al, 2020; Dong et al, 2019; Efesoy et al, 2018; Farook et al, 2021; Gurtner et al, 2017; Hatzimouratidis, 2007; Irfan et al, 2020; Ismail et al, 2019; Lau et al, 2008; Li et al, 2017, 2019; Mulhall et al, 2011; Punjani et al, 2018; Raina et al, 2007; Tsai et al, 2017; Ulloa et al, 2008; Walther et al, 2017; Wentzell et al, 2017).…”
mentioning
confidence: 99%
“…Regular goserelin acetate administration is the pharmacological treatment of choice in patients with recurrent priapism due to its antagonistic action on testosterone plasma levels. 61 …”
Section: Resultsmentioning
confidence: 99%